Răspuns :
[(3a+19):5-2]×11=35-2
[(3a+19):5-2]×11=33
(3a+19):5-2=33:11
(3a+19):5-2=3
(3a+19):5=5
3a+19=5×5
3a+19=25
3a=25-19
3a=6
=2
[(3a+19):5-2]×11=33
(3a+19):5-2=33:11
(3a+19):5-2=3
(3a+19):5=5
3a+19=5×5
3a+19=25
3a=25-19
3a=6
=2
[(3a+19):5-2]×11+2=35
[(3a+19):5-2]×11=35-2
[(3a+19):5-2]×11=33
(3a+19):5-2=33:11
(3a+19):5-2=3
(3a+19):5=3+2
(3a+19):5=5
3a+19=5×5
3a+19=25
3a=25-19
3a=6
a=6:3
a=2
[(3a+19):5-2]×11=35-2
[(3a+19):5-2]×11=33
(3a+19):5-2=33:11
(3a+19):5-2=3
(3a+19):5=3+2
(3a+19):5=5
3a+19=5×5
3a+19=25
3a=25-19
3a=6
a=6:3
a=2